2011
DOI: 10.1097/ta.0b013e3181f30fb0
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Preconditioning and N-Acetylcysteine on Oxidative Stress Resulting From Tourniquet-Induced Ischemia-Reperfusion in Arthroscopic Knee Surgery

Abstract: Tourniquet-induced IR period in routine arthroscopic knee surgery resulted in oxidative stress by increasing MDA, SOD, GSH-Px, TOS and decreasing TAC. NAC and IPC had protective effect on occurrence of oxidative stress resulting from IR period by preventing MDA, SOD, GSH-Px, TAC, and TOS changes in routine arthroscopic knee surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 48 publications
0
37
0
1
Order By: Relevance
“…Silymarin significantly enhanced SOD and GPX levels and decreased hs-CRP compared to the control. TAC levels as an indicator of the overall protective effect of antioxidants in body fluids, on cell membranes and other components of cells against oxidative damage (Koca et al 2011) were elevated in the silymarin supplementation group compared to the placebo. Additionally, a significant decrease was observed in serum levels of MDA in the silymarin group compared to the baseline.…”
Section: Discussionmentioning
confidence: 87%
“…Silymarin significantly enhanced SOD and GPX levels and decreased hs-CRP compared to the control. TAC levels as an indicator of the overall protective effect of antioxidants in body fluids, on cell membranes and other components of cells against oxidative damage (Koca et al 2011) were elevated in the silymarin supplementation group compared to the placebo. Additionally, a significant decrease was observed in serum levels of MDA in the silymarin group compared to the baseline.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, muscle mitochondrial dysfunction was recently shown to be associated with 5-year survival in patients with peripheral arterial disease, underlining its clinical significance [11]. Ischemic preconditioning (i.e., short bouts of nondamaging periods of ischemia and reperfusion before long-lasting index ischemia) provides muscular protection with improved mitochondrial function and decreased oxidative stress in young animals [12] or young healthy patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…One study used both anaesthetic and antioxidant intervention (propofol and N‐acetyl‐cysteine) (Table ). Three studies used ischaemic pre‐conditioning (Table ) and one study used both ischaemic pre‐conditioning and antioxidant intervention (N‐acetyl‐cysteine) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…One study examined both propofol and N‐acetyl‐cysteine, but propofol was used in a sub‐anaesthetic dose and we therefore categorised it in the antioxidant intervention group . In one study that both used antioxidant intervention (N‐acetyl‐cysteine) and ischaemic pre‐conditioning, the authors found that ischaemic pre‐conditioning was superior to N‐acetyl‐cysteine in protecting against ischaemia–reperfusion injuries; we therefore chose to categorise this study in the ischaemic pre‐conditioning group (Table ). It will, however, also be briefly described in this section.…”
Section: Resultsmentioning
confidence: 99%